Diabetes and Sepsis: Risk, Recurrence, and Ruination - Frydrych, Lynn M.; Fattahi, Fatemeh; He, Katherine; Ward, Peter A.; Delano, Matthew J. (Frontiers in Endocrinology, 2017)
Sepsis develops when an infection surpasses local tissue containment. A series of dysregulated physiologic responses are generated, leading to organ dysfunction and a 10% mortality risk. When patients with sepsis demonstrate elevated serum lactates and require vasopressor therapy to maintain adequate blood pressure in the absence of hypovolemia, they are in septic shock with an in-hospital mortality rate greater than 40%. With improvements in intensive care treatment strategies, overall sepsis mortality has diminished to approximately 20% at 30 days; however, mortality continues to steadily climb after recovery from the acute event. Traditionally, it was thought that the complex interplay between inflammatory and anti-inflammatory responses led to sepsis-induced organ dysfunction and mortality. However, a closer examination of those who die long after sepsis subsides reveals that many initial survivors succumb to recurrent, nosocomial, and secondary infections. The co-morbidly challenged, physiologically frail diabetic individuals suffer the highest infection rates. Recent reports suggest that even after clinical “recovery” from sepsis, persistent alterations in innate and adaptive immune responses exists resulting in chronic inflammation, immune suppression, and bacterial persistence. As sepsis-associated immune defects are associated with increased mortality long-term, a potential exists for immune modulatory therapy to improve patient outcomes. We propose that diabetes causes a functional immune deficiency that directly reduces immune cell function. As a result, patients display diminished bactericidal clearance, increased infectious complications, and protracted sepsis mortality. Considering the substantial expansion of the elderly and obese population, global adoption of a Western diet and lifestyle, and multidrug resistant bacterial emergence and persistence, diabetic mortality from sepsis is predicted to rise dramatically over the next two decades. A better understanding of the underlying diabetic-induced immune cell defects that persist following sepsis are crucial to identify potential therapeutic targets to bolster innate and adaptive immune function, prevent infectious complications, and provide more durable diabetic survival.